EFEKTIFITAS BUAH JERUK SIEM MADU DALAM MENGURANGI PEMBENTUKAN PLAK - silvia tok (Fakultas Kedokteran Gigi Universitas Sumatera Utara, 2013)
Abstract Citrus fruits are produced in many countries around the world. Some of the researches showed that citrus fruits contain significant antimicrobial activity towards bacteria in mouth so it could reduce the plaque formation because its polyphenol compound like tannin and naringin. Tannin can inhibit bacteria growth with the strong binding iron capacity and also inhibit the adhesive of Streptococcus to the enamel surface. Naringin is effective in inhibit the growth of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis significantly. The aim of the study is to analyze the effectiveness of citrus fruits in reducing the plaque formation. This is an experimental study with time series design. Total samples of 35 students of Faculty of Dentistry University of North Sumatera were selected with systematic random sampling. They were being control for the first 10 days as control group and the same sample were continue to be treated as treatment group for 10 days. When they were in treatment group, all of the samples were instructed to consume the citrus fruit once a day. Loe&Silness plaque index is used to measure the plaque index score. The result of this research showed that increase of the plaque index in treatment group is lower than control group. It means siem madu citrus fruit is effective in reducing the plaque formation. The citrus fruit might reduce the plaque formation because the mechanical effect of its fiber in removing plaque and also the chemical effect of its substrates. Key words: siem madu, citrus fruit, plaque formation